Causal relationship between nuclear energy, carbon-di-oxide emission and economic growth. Empirical evidence from China - Wu, Jinchi; Fu, Qinghua; Sial, Muhammad Safdar; Pavel, Codruta—Daniela; Samad, Sarminah; Matac, Liviu Marian (Frontiers in Energy Research, 2022)
The present study aims to explore the role of nuclear energy production in aiding the sustainable economic growth of Chine by exploring the underlying causal relationship between reducing CO2 ¬emissions and nu-clear energy production. The study also aims to explore the relationship between economic growth and nu-clear energy production in the Chinese context. Besides that, the present research also provides evidence in favor of nuclear energy in terms of controlling the overall emissions target of the Chinese government. The main aim of the present research is to investigate the effect of the use of nuclear energy on Chinese CO2 emissions and its contribution to the growth of Chinese G.D.P. by utilizing the data from 1992 to 2020. Using a modified Granger causality test, the present research identified one-way causation between the usage of nuclear energy and emissions of CO2. Based on the research findings, it can be argued that by utilizing nuclear power, China can control the emissions of greenhouse gasses, to meet the global emission targets.